ANALISIS NILAI KARAKTER KREATIF DALAM BUKU BAHASA INDONESIA KELAS 4 KURIKULUM MERDEKA - Mujiana, Dewi Maryamitha; Prasetyowati, Dina; Habsari, Novi (Kurikula : Jurnal Pendidikan, 2024)
This study aims to determine the creative character values contained in the grade4 Indonesian language textbook of the Merdeka Curriculum. This research is a qualitative studyusing the text analysis method to study textbooks. The data of this research is the content of the creativity element of the Grade 4 Indonesian language textbook of the Merdeka Curriculum.Based on the analysis, the Indonesian language book for grade 4 of the Merdeka Curriculumcontains creative character values in Chapters I, II, III, IV, V, VII, and VIII. This can be seenfrom the creative elements included in each chapter. However, this element is not found inChapter VI because the focus is more on mastering the material